Unemployment Anxiety and its Relationship to Effective Self-efficacy among Final Year Students at Al- Quds University - Iyad Ishtaya, Iyad; Shaheen, Mohammed (Jordan Journal of Educational Sciences, 2015)
The study aimed to investigate the level of unemployment anxiety among senior students at Al- Quds University in light of some variables such as sex, faculty, and academic attainment, as well as the relationship between them. The study used a descriptive approach by applying the scales on a stratified random sample including (288) students, representing (11%) of the (2503) community, where (1113) males, representing about (45%) of the whole community, and (1390) females, representing (55%). The results showed that the level of both unemployment anxiety and effective self-efficacy was moderate, and there was a negative correlation between unemployment anxiety and the effective self-efficacy among students. The results also indicated the absence of significant differences in the rates of unemployment anxiety among students according to sex and academic average, while the differences in general anxiety field were in favor of the medical and nursing faculties students, compared to students of other faculties